Quantitative interpretation of ToxTracker dose–response data for potency comparisons and mode‐of‐action determination. (2nd February 2023) - Boisvert, Lorrie; Derr, Remco; Osterlund, Torben; Hendriks, Giel; Brandsma, Inger
Abstract: ToxTracker is an in vitro mammalian stem cell‐based reporter assay that detects activation of specific cellular signaling pathways (DNA damage, oxidative stress, and/or protein damage) upon chemical exposure using flow cytometry. Here we used quantitative methods to empirically analyze historical control data, and dose–response data across a wide range of reference chemicals. First, we analyzed historical control data to define a fold‐change threshold for identification of a significant positive response. Next, we used the benchmark dose (BMD) combined‐covariate approach for potency ranking of a set of more than 120 compounds; the BMD values were used for comparative identification of the most potent inducers of each reporter. Lastly, we used principal component analysis (PCA) to investigate functional and statistical relationships between the ToxTracker reporters. The PCA results, based on the BMD results for all substances, indicated that the DNA damage ( Rtkn, Bscl2 ) and p53 ( Btg2 ) reporters are functionally complementary and indicative of genotoxic stress. The oxidative stress ( Srxn1 and Blvrb ) and protein stress ( Ddit3 ) reporters are independent indicators of cellular stress, and essential for toxicological profiling using the ToxTracker assay. Overall, dose–response modeling of multivariate ToxTracker data can be used for potency ranking and mode‐of‐action determination. In the future, IVIVE (in vitro to in vivo extrapolation) methods can be employed to determine in vivo AED (administered equivalent dose) values that can in turn be used for human health risk assessment.